Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1111/j.1365-2249.1995.tb06658.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect on immunity of long-term intensive training in elite swimmers

Abstract: SUMMARYThe impact of long-term training on systemic and mucosal immunity was assessed prospectively in a cohort of elite swimmers over a 7-month training season in preparation for national championships. The results indicated significant suppression (P < 0-05) of serum IgA, IgG and IgM and salivary IgA concentration in athletes associated with long-term training at an intensive level. There was also a trend towards lower IgG2 subclass levels in serum in athletes compared with controls (P = 0 07). There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
118
4
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 24 publications
10
118
4
10
Order By: Relevance
“…Studies carried out in human elite athletes found lower levels of salivary IgA to be associated with increased incidence of respiratory illness (Gleeson et al, 1995;Gleeson and Pyne, 2000;Mackinnon, 2000). Our data show that IgA levels are lower in animals kept under intensive physical training and cleaner facilities, which are conditions that correlate with lower mucosal immunity in several species.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Studies carried out in human elite athletes found lower levels of salivary IgA to be associated with increased incidence of respiratory illness (Gleeson et al, 1995;Gleeson and Pyne, 2000;Mackinnon, 2000). Our data show that IgA levels are lower in animals kept under intensive physical training and cleaner facilities, which are conditions that correlate with lower mucosal immunity in several species.…”
Section: Discussionmentioning
confidence: 48%
“…In humans, intense exercising causes a significant decrease in IgA and IgM levels in serum (Mackinnon, 2000). As a consequence, elite athletes are more susceptible to respiratory and gastrointestinal tract disorders when compared to non-athletic individuals and are considered bearers of 'chronic mild immunosuppression' (Gleeson et al, 1995;Gleeson and Pyne, 2000). In horses, it has been shown that intensive exercise triggers an increase in cortisol and ACTH levels (Vara et al, 2006), a decrease in number of CD81 T lymphocytes (Malinowski et al, 2004), and is associated with higher incidence and morbidity of Babesia equi (al-Ani et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Glesson et al 6 reported that in athletes, in a swimming training season, there were not significant alterations in the number or percentages of B or T cells subgroups; however, significant decrease in the number and percentage of natural killer cells was observed. Conversely, a study by Pedersen et al 14 , in which trained cyclists were compared with untrained men, the percentage of NK cells was higher in the trained athletes, but the study does not report in which training phase the data were collected.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of physical training over the number and function of natural killer cells (NK) is still discussed. While intervention or cross-sectional studies reported moderate increase in cytotoxicity of NK cells (NKCC) after moderate physical training 5 , intense training has shown the capacity to alter subgroups of NK cells as well as to reduce NKCC 6,7 . The NK cells represent an intrinsic component of immunity which can destroy tumor and virus-infected cells with no previous sensibilization (i.e., non-MHC restricted) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they concluded that the controlled trial showed no effect of aerobic exercise on in vitro immune function, despite excellent retention, high adherence, and demonstrable efficacy of the exercise intervention. However, intense training has been shown to alter NK cell subsets and reduce NKCC [34,35].…”
Section: Open Accessmentioning
confidence: 99%